Isolation and characterization of a mixed bacterial consortium isolated from the Juru River, Malaysia in decolourising azo dye (Reactive Red 120) - Manogaran, Motharasan (2021)
The application of microorganisms in Reactive Red 120 (RR120) remediation has gained significant attention. Textile effluents containing RR120 is known for its carcinogenicity and mutagenicity. The major issue in the biodegradation of RR120 by microorganisms is it is very difficult to isolate microorganisms able to utilise the dye as a carbon source as this can completely mineralized the dye. This study investigates and compares the role of methods and media used in obtaining bacterial consortia capable of decolourising RR120 as the sole carbon source, which is extremely rare to find. Three RR120-decolourising consortia were isolated from contaminated water samples from the Juru River, Malaysia. Only consortium JR3 was able to decolourise RR120 as a sole carbon source compared to the rest of the consortium. Based on 16S rRNA gene sequence analysis and biochemical test, consortium JR3 consists of Pseudomonas aeruginosa strain MM01, Enterobacter sp. strain MM05 and Serratia marcescens strain MM06. It was found that a mix of the bacterial consortium JR3 was able to decolourise RR120 much faster compared to single strains of MM01, MM05 and MM06. Initially, consortium JR3 was able to decolourise 42.5% of 50 ppm RR120 within 24 h of incubation. Using one-factor-at-time optimisation processes, the consortium JR3 was enhanced to decolourise 88.2% of 50 ppm RR120 within 24 h. The result illustrates that yeast extract at 0.7 g/L, ammonium sulphate at 0.75 g/L, phosphate buffer with pH 8, the temperature at 35°C and RR120 concentration at 200 ppm as the optimum decolourisation conditions required by consortium JR3. Meanwhile, based on statistical optimisation using Response surface methodology (RSM), ammonium sulphate 0.645 g/L, pH 8.293, 200.1 ppm of RR120, temp 34.53°C results in a decolourisation rate of 93.34% at 48 h. Discriminatory statistical analysis in modelling studies illustrates that the best primary model was the modified Gompertz model, while the secondary model was best suited by Aiba. The ability of consortium JR3 to decolourise RR120 under the presence of heavy metals such as silver, arsenic, cadmium, chromium, copper, mercury, lead, and zinc were also investigated in this study. It was found that chromium had the least effect on RR120 decolourisation followed by zinc and lead. Meanwhile, 1 ppm mercury has the highest inhibitory effect on consortium JR3, therefore, reducing decolourisation of 200 ppm RR120 by 32.5%. The consortium was able to tolerate up to 10 ppm of chromium and 1 ppm of mercury. The decolourised RR120 product showed less inhibition effect on Vigna radiata’s seed germination compared to the parent compound, suggesting that RR120 toxicity has been reduced. RR120 at the lowest concentration of 25 ppm reduced seed germination by 17.7%, shoot length by 1.13 cm and root length by 1.43 cm. The decolourised product of 25 ppm RR120 illustrated no significant difference (p>0.05) to control. In conclusion, the consortium JR3 has the potential to be used in the management of RR120 contamination in the environment. Consortium JR3 was not only able to decolourise at high concentrations of 500 ppm RR120, but the end product is safer compared to the parent compound alone in Vigna radiata toxicity studies